Analisis Poskolonial Novel Gadis Kretek Karya Ratih Kumala - Nadya Salsabila; Windy Febriyanti Nabila; Egi Fahira Tuhfa; Muhammad Isman (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The purpose of this study is to analyze the use of mimetic and subaltern forms carried out by the ruling class against the ruling class in the colonial setting of the novel Gadis Kretek by Ratih Kumala. The main source of this research material is the novel Gadis Kretek by Ratih Kumala which was published in 2019 and owned by PT Gramedia Pustaka Utama, a Jakarta-based company. The research data covers the origins of the novel in a postcolonial framework, social structure, epistemology, and the study of human behavior. The data of this study are qualitative, and descriptive statistics are used as a methodology. Documentation serves as a tool for collecting data in research. The findings of this study show that the magical realism depicted in the novel Gadis Kretek by Ratih Kumala has implications for various aspects of social organization, knowledge, and consciousness. Second. Ratih Kumala's novel Gadis Kretek depicts various categories of subalterns, such as those that arise from their interactions with oppressors and elite-subalterns.